2016
DOI: 10.1038/ncomms10806
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical reconstitution of TET1–TDG–BER-dependent active DNA demethylation reveals a highly coordinated mechanism

Abstract: Cytosine methylation in CpG dinucleotides is an epigenetic DNA modification dynamically established and maintained by DNA methyltransferases and demethylases. Molecular mechanisms of active DNA demethylation began to surface only recently with the discovery of the 5-methylcytosine (5mC)-directed hydroxylase and base excision activities of ten–eleven translocation (TET) proteins and thymine DNA glycosylase (TDG). This implicated a pathway operating through oxidation of 5mC by TET proteins, which generates subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
158
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 51 publications
10
158
0
4
Order By: Relevance
“…Consistently, TET1 and TDG were found to interact physically [27,98] and to be coordinated or targeted to chromatin by accessory factors such as Gadd45a (Fig. 2) [99, 100].…”
Section: Genomic Regions Enriched For 5fc and 5cac In Tdg-deficient Ementioning
confidence: 94%
“…Consistently, TET1 and TDG were found to interact physically [27,98] and to be coordinated or targeted to chromatin by accessory factors such as Gadd45a (Fig. 2) [99, 100].…”
Section: Genomic Regions Enriched For 5fc and 5cac In Tdg-deficient Ementioning
confidence: 94%
“…Alternatively, the mutagenic effect could result from the deamination of 5-mC in cooperation with its oxidation by TET2. Indeed, it has recently been shown that TET1-TDG-BER pathway could favor C > T mutagenesis when deamination of 5-mC and TET-induced oxidation of 5-mC to 5-caC occur simultaneously in the symmetrically methylated CpG [42]. This phenomenon could be enhanced in the absence of TDG.…”
Section: Impact Of Tet2-induced 5-hmc On Mutagenesismentioning
confidence: 96%
“…8,9 Results from studies such as those demonstrating in vitro recognition and excision of 5f C and 5ca C by thymine-DNA glycosidase (TDG), and increased levels of the two modifications in mouse embryonic stem cells lacking TDG, supported the notion that the oxidized species might merely be intermediates in the active reversion of the 5m C mark. [10][11][12] However, recent data revealing the association of 5hm C, 5f C, and 5ca C with regulatory elements have led to the hypothesis that they might have their own roles in gene regulation. 11,13,14 This is supported by enrichmentbased and single-base resolution sequencing studies, which show 5hm C, 5f C, and 5ca C to be enriched at various promoter, enhancer, and exon sites.…”
mentioning
confidence: 97%